2012
DOI: 10.1093/treephys/tps052
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the intra-annual wood formation of three European species (Fagus sylvatica, Quercus petraea and Pinus sylvestris) as related to leaf phenology and non-structural carbohydrate dynamics

Abstract: Monitoring cambial phenology and intra-annual growth dynamics is a useful approach for characterizing the tree growth response to climate change. However, there have been few reports concerning intra-annual wood formation in lowland temperate forests with high time resolution, especially for the comparison between deciduous and coniferous species. The main objective of this study was to determine how the timing, duration and rate of radial growth change between species as related to leaf phenology and the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
241
1
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 326 publications
(279 citation statements)
references
References 57 publications
30
241
1
7
Order By: Relevance
“…These references document distinct patterns among tree functional types with regard to the relative onsets of cambium division and leaf appearance. In the majority of diffuse-porous trees, the onset of cambium division occurs simultaneously with or a few days after budburst (Suzuki et al 1996;Čufar et al 2008;Michelot et al 2012;Prislan et al 2013), though delays of several weeks have been observed in a number of species (e.g., as long as 8 weeks in Carpinus betulus; Delaporte (2010)). Ring-porous trees are relatively more vulnerable to freezing-induced embolism than diffuse-porous species (Cochard and Tyree 1990).…”
Section: Integrated Phenology At the Tree Scalementioning
confidence: 99%
See 1 more Smart Citation
“…These references document distinct patterns among tree functional types with regard to the relative onsets of cambium division and leaf appearance. In the majority of diffuse-porous trees, the onset of cambium division occurs simultaneously with or a few days after budburst (Suzuki et al 1996;Čufar et al 2008;Michelot et al 2012;Prislan et al 2013), though delays of several weeks have been observed in a number of species (e.g., as long as 8 weeks in Carpinus betulus; Delaporte (2010)). Ring-porous trees are relatively more vulnerable to freezing-induced embolism than diffuse-porous species (Cochard and Tyree 1990).…”
Section: Integrated Phenology At the Tree Scalementioning
confidence: 99%
“…In certain ring-porous species (deciduous oaks), the onset of cambial division is the first step of spring resumption (Gričar 2010;González-González et al 2013), whereas in others (e.g., Fraxinus excelsior), overwintering vessels start to enlarge before budburst (SassKlaassen et al 2011) and cambial division is resumed after budburst (Frankenstein et al 2005). In conifers, the resumption of cambium activity generally occurs before budburst (Rossi et al 2009;Gruber et al 2010;Cuny et al 2012;Michelot et al 2012;Huang et al 2014).…”
Section: Integrated Phenology At the Tree Scalementioning
confidence: 99%
“…As demonstrated by Steppe & Lemeur (2004) and Michelot et al (2012), growth of both juvenile and mature beech trees was drought sensitive. Suffi cient water uptake ensures cell turgor pressure which is the main force providing cell expansion and division (Lockhart, 1967).…”
Section: Introductionmentioning
confidence: 94%
“…Earlier growth onset for DT can be explained by higher root competitiveness of dominant trees which are very competitive, ensuring better water absorption (Le Goff & Ottorini, 2001). During the observation period, cumulative changes of stem diameter formed a sawblade shaped curve with fl uctuations caused by daily variations of wood hydration (Steppe & Lemeur, 2004;Michelot et al, 2012). Pronounced leaps, corresponding to rain events and/or a decrease in VPD and air temperature, are distinguished as phases of increment.…”
Section: Lemeur 2004)mentioning
confidence: 99%
See 1 more Smart Citation